Note from the Editor - Adendorff, SA (The South African Journal of Industrial Engineering, 2013)
As reported in the November 2012 edition of the South African Journal of Industrial Engineering (SAJIE), the open access on-line presence of SAJIE became a reality during that month. In its previous guise, SAJIE would be mailed to the members of the Southern African Institute for Industrial Engineering (typically between 600 and 700 members) of which only a few were based outside of South Africa. On the day that the new on-line presence realised, a Google Analytics account was set up to monitor the traffic to the SAJIE website. By the end of April 2013, the website had received more than 9 500 visits from almost 5 900 unique visitors representing 125 countries of the world. The on-line presence of SAJIE has catapulted the Journal into the global arena.